2003
DOI: 10.2135/cropsci2003.2089
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and Productivity of Old and Modern Durum Wheats in a Mediterranean Environment

Abstract: Genetic variability of leaf net photosynthesis rate (An) and its relation to productivity in durum wheat (Triticum turgidum L. var. durum) is not well defined. Two field experiments were conducted at the experimental area of the Faculty of Agriculture, in the University of Çukurova, Turkey, to evaluate the differences between old and modern cultivars in An and productivity. Experiments with sowing dates in November 1996 and February 1997 were performed under rainfed and irrigated conditions, respectively. Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Nevertheless, Taewa exhibited exceptionally high photosynthetic WUE characteristics under water stress. This ability suggests they are well adapted to low water supply as once reported in old wheat compared to their modern wheat [30] and among potato genotypes [31].…”
Section: Discussionsupporting
confidence: 58%
“…Nevertheless, Taewa exhibited exceptionally high photosynthetic WUE characteristics under water stress. This ability suggests they are well adapted to low water supply as once reported in old wheat compared to their modern wheat [30] and among potato genotypes [31].…”
Section: Discussionsupporting
confidence: 58%
“…In North China, kernel weight of bread wheat was not modified between the sixties and the year 2000 (Zhou et al, 2007). But, in durum wheat growing in a Mediterranean environment in Turkey, kernel weight was superior in modern cultivars (Koç et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Koc et al . (2003) indicated a high correlation between stomatal conductance and photosynthesis rate per unit leaf area 26 . Using cold helium plasma at the booting stage, it was observed that the treated wheat had more length and stronger roots as the key factors to increase absorption of water and nutrition 27 .…”
Section: Discussionmentioning
confidence: 98%